2018
DOI: 10.1002/adsc.201801143
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Asymmetric Hydrogenation of N‐Alkyl α‐Aryl Furan‐Containing Imines: an Efficient Route to Unnatural N‐Alkyl Arylalanines and Related Derivatives.

Abstract: High throughput experimentation (HTE) has enabled the rapid identification of ligand/ precatalyst combinations that facilitate highly enantioselective hydrogenations of prochiral N-alkyl aaryl ketimines containing a furyl moiety. The chiral amines obtained have proven to be modular precursors in the synthesis of unnatural mono Nalkylated arylalanines and related derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…They accessed unnatural N-alkylated phenylalanine analogs via asymmetric hydrogenation of N-alkyl imine precursors in presence of an iridium catalyst. [139] A recent breakthrough in SF 5 -tagging of proteins has been reported by Huber and co-workers. They disclosed the genetic encoding of SF 5 -phenylalanine 168 via newly developed aminoacyl-tRNA synthetases that allow site-specific incorporation into protein chains with high yields.…”
Section: Pentafluorosulfanyl Group In Medicinal Chemistrymentioning
confidence: 98%
“…They accessed unnatural N-alkylated phenylalanine analogs via asymmetric hydrogenation of N-alkyl imine precursors in presence of an iridium catalyst. [139] A recent breakthrough in SF 5 -tagging of proteins has been reported by Huber and co-workers. They disclosed the genetic encoding of SF 5 -phenylalanine 168 via newly developed aminoacyl-tRNA synthetases that allow site-specific incorporation into protein chains with high yields.…”
Section: Pentafluorosulfanyl Group In Medicinal Chemistrymentioning
confidence: 98%
“…Enantioselective hydrogenation [68] to rapidly identify the choice of ligand and precatalyst combination for N‐alkyl α‐aryl ketimines containing a furyl group to give the challenging N‐alkyl D‐enantiomer has been performed in high throughput (Scheme 5a). A screen of asymmetric catalysts including (Rh, Ru, Ir precursors with sulfonated diamine ligand) gave an enantiomeric ratio of 83 : 13.…”
Section: Asymmetric Hydrogenation Reactionsmentioning
confidence: 99%
“…The f -binaphane ligand ( L27 ) has been also employed by Mazuela, Johansson and co-workers to achieve the enantioselective hydrogenation of N -alkyl α-aryl ketimines bearing a furyl moiety which are interesting scaffolds easily convertible into valuable chiral N -alkylated phenylalanine analogues (Scheme ). Large screening of various phosphine ligands revealed that L27 was the most efficient in AIH of this particular skeleton. Under 30 atm of H 2 , the corresponding chiral amines were obtained with moderate to good enantioselectivities and with good to excellent yields.…”
Section: Iridium-based Catalystsmentioning
confidence: 99%